Who are the convoys of the happiness of Chinese urban residents? Research on social relations and subjective well-being based on the convoy model - Li, Jianna; Guo, Bin; Lu, Mengyuan; Zhang, Wen (Frontiers in Psychology, 2023)
While the rapid advancement of urbanization has driven the improvement of material living standards, it has also brought about rapid social changes and intensified competition. In this "involutive" environment characterized by highly competitive and strong pressure, urban residents tend to fall into a state of "mental exhaustion." Anxiety, depression, sleep disorders, and other mental illnesses have become serious threats to public health in Chinese cities. Support from social relations is crucial for enhancing residents' subjective well-being (SWB) and promoting their mental health, especially in the context of China's highly contextualized collectivist culture. Based on the convoy model of social relations and data from the Chinese General Social Survey (CGSS) 2018, this paper focuses on residents' SWB convoys and their relationships. The study finds that kinship and friendship are Chinese urban residents' SWB convoys, and there is an obvious substitution effect between these two factors. However, there is no significant correlation found between neighborhood and SWB, which may be related to neighborhood indifference caused by China's housing system reform. From the perspective of an individual's life course, there is heterogeneity in the SWB convoys of different age groups. The SWB convoys of young and middle-aged groups consist of kinship and friendship, while those of elderly people include kinship and neighborhood. In addition, both relative income and social class significantly weaken the contribution of kinship to residents' SWB, which means that for the poor individuals living at the bottom of society, support from kinship is the most important source of social capital. These findings provide new insights into the relationship between social relations and the welfare of Chinese urban residents and have implications for not only improving the social support network of Chinese urban residents but also continuously improving national SWB through intervention implementation.